Role of Public Relations in Corporate Social Responsibility: An Empirical Study - Sharma, Karishma; Mohanty, Shiba Prasad; Longani, Kirti Dang (Procedia of Social Sciences and Humanities, 2024)
This exploration paper digs into the essential job of advertising (PR) inside the domain of corporate social obligation (CSR). In the present unique business scene, CSR has arisen as a basic part for associations planning to upgrade their standing, form partner trust, and contribute decidedly to society. PR goes about as the essential channel through which organizations convey their CSR drives, drawing in with different partners and moulding discernments. This paper looks to explain the diverse connection among PR and CSR, inspecting how PR methodologies impact CSR rehearses, discernment the board, and authoritative authenticity. Through a far-reaching examination of hypothetical structures, contextual investigations, and industry bits of knowledge, the exploration expects to reveal insight into the essential objectives and difficulties related with incorporating PR into CSR tries. At last, the discoveries of this study add to a more profound comprehension of how PR fills in as an impetus for advancing corporate social obligation and encouraging feasible strategic policies.